Оптимізація точності прогнозування співвідношення руда/вода в кульовому млині з циркулюючим навантаженням - Кондратець, В. О.; Сербул, О. М.; Kondratets, Vasily; Serbul, Alexander (КНТУ, 2016)
Вибір пристроїв вимірювання технологічних параметрів за похибкою можливо подати як задачу оптимізації відповідно методу динамічного програмування у три стадії, у кожній з яких обирається один з засобів. В процесі оптимізації при відносній похибці вимірювання витрати пульпи у пісковому жолобі ±3,0 % відносна максимальна похибка прогнозування співвідношення руда/вода склала 1,72 % при визначенні витрати руди і води в млин з похибкою ±1,0 % порівняно з допустимою ±3,0 %. The purpose of the article is a search for the best combination of precision instruments for the margin of error prediction liquefaction. The ratio of the ore/water predict possible in accordance with this algorithm on the measured parameters - ore and water consumption in a ball mill, a volume flow of ore and water in a ball mill, a volume flow of sand in sand classifier chute. The measurement error of each parameter introduces an error in the final result. he task is complicated by the fact that the volumetric flow of sand in the sand chute accurately measure is not possible, which significantly reduces the result of forecasting where the measurement error or most approximates the boundary permissible value of ± 3,0% for the ratio of ore/water. Selection device for measuring process parameters of error may be represented as the optimization problem by the method of dynamic programming in three stages, each of which selects one means. In the process of optimizing the relative error of flow measurement in sand chute ± 3,0%, the maximum relative error of prediction ratio of ore / water amounted to 1.72% as determined by the flow of ore and water in the mill with an accuracy of ± 1,0% compared with the allowable ± 3 0%.
Optimization of forecasting accuracy ratio ore/water in a ball mill with a circulating load
Keywords: кульовий млин; співвідношення руда/вода; прогнозування; точність; оптимізація; ball mill; the ratio of ore/water; forecasting; accuracy; optimization